Animal manure-derived biochars produced via fast pyrolysis for the removal of divalent copper from aqueous media. (1st May 2018) - Idrees, Muhammad; Batool, Saima; Kalsoom, Tanzila; Yasmeen, Summera; Kalsoom, Amna; Raina, Sadaf; Zhuang, Qiang; Kong, Jie
Abstract: Here, we report a pyrolyzed guinea fowl manure-derived biochar (GFM-BC) and cattle manure-derived biochar (CTM-BC) and their use as adsorbent for the removal of divalent copper from aqueous media was evaluated. The BCs physical and chemical properties were characterized by Scanning electron microscopy (SEM), Elemental dispersive x-ray analysis (EDX), Fourier transform infrared microscopy (FTIR) and thermo gravimetric analysis (TGA). The results presented that the BCs obtained higher content were quite effective for Cu (II) removal with maximum capacities of 43.60 and 44.50 mg g −1 for GFM-BC and CTM-BC, respectively. From simulation of experimental data with different adsorption isotherms and kinetics models it was found that the adsorption of both BCs was adequately fitted by Freundlich adsorption model and pseudo-second order kinetic model, respectively. Thermodynamic parameters suggested that the adsorption of Cu (II) onto both BCs was feasible, spontaneous and exothermic under evaluated parameters. Thus, the biomass used in this study proved to be effective adsorbents for the removal of Cu (II) from aqueous media. Highlights: Biochar, a by-product of fast pyrolysis, was prepared as a low cost adsorbent precursor. Effect of derived biochars on divalent copper removal efficiency was investigated. CTM-BC and GFM-BC characteristics were analyzed. Langmuir and Freundlich models were used for equilibrium modeling. Adsorption data agreed well with a pseudo-second-order kinetic model.